High-School Students’ Beliefs about Oral Corrective Feedback in EFL Classroom: A Survey Study - Fadhila Intan Mawarni; Banatul Murtafi’ah (SALEE: Study of Applied Linguistics and English Education, 2023)
Making mistakes is a typical occurrence for language learners, and it is also a necessary component of the learning process, especially in learning English as a foreign language. Mistakes or errors that often occur if not immediately corrected will affect their communication and focus in learning English. Error correction is still debated whether what kind of error should be corrected and who has more right to give oral corrective feedback (OCF). Therefore, this study aims to investigate students' beliefs about the target and source of oral corrective feedback (OCF). This study used a quantitative method with 226 students from public senior high school as respondents in the study. This study used an instrument called Students beliefs about target and sources of OCF developed by Ha and Nguyen (2021). There were 17 items which were divided into 2 aspects (i.e., target and sources). The data were then analyzed by using SPSS and Microsoft Excel. In conclusion, Students believed that all forms of errors, particularly those affecting communication, should be corrected. However, they also emphasized that mistakes should be corrected even if they did not interfere with communication or the lesson. Moreover, This study also discovered that students wished their teachers had provided them an opportunity to practice offering feedback to each other and to encourage self-correction because it was beneficial. The result showed that students were positive in receiving all kinds of errors to be corrected and show that the teacher is not the only one who can provide feedback to them.